Aerosolized amphotericin B as prophylaxis for invasive pulmonary aspergillosis: a meta-analysis. (January 2015) - Xia, Di; Sun, Wen-Kui; Tan, Ming-Ming; Zhang, Ming; Ding, Yuan; Liu, Zhi-Cheng; Su, Xin; Shi, Yi
Highlights: Animal studies showed lower overall mortality rates among animals that underwent aerosolized amphotericin B (AMB) prophylaxis (odds ratio (OR) 0.13, 95% confidence interval (CI) 0.08–0.21). Clinical trials showed a lower incidence of invasive pulmonary aspergillosis (IPA) among patients who underwent aerosolized AMB prophylaxis (OR 0.42, 95% CI 0.22–0.79). The prophylactic use of aerosolized AMB is effective in reducing the mortality of immunosuppressed animals. The prophylactic use of aerosolized AMB is associated with a lower rate of IPA among high-risk patients. Summary: Objectives: Invasive pulmonary aspergillosis (IPA) is associated with high mortality in high-risk (immunosuppressed) patients. Many studies have investigated whether prophylactic inhalation of amphotericin B (AMB) reduces the incidence of IPA, but no definitive conclusions have been reached. The present meta-analysis was performed to evaluate the efficacy of prophylactic inhalation of AMB for the prevention of IPA. Methods: MEDLINE and other databases were searched for relevant articles published until December 2013. Randomized controlled trials that compared aerosolized AMB with placebo were included. Two reviewers independently assessed and extracted the data of all trials. Results: Six animal studies and two clinical trials involving 768 high-risk patients were eligible. The animal studies showed lower overall mortality rate among animals that underwent aerosolized AMB prophylaxis (odds ratio (OR) 0.13, 95% confidence interval (CI) 0.08–0.21). Similarly, the clinical trials showed a lower incidence of IPA among patients who underwent aerosolized AMB prophylaxis (OR 0.42, 95% CI 0.22–0.79). Conclusions: This analysis provides evidence supporting the notion that the prophylactic use of aerosolized AMB effectively reduces the incidence of IPA among high-risk patients.